An injectable hydrogel material, preparation method thereof and application as a vitreous substitute

By developing injectable hydrogel materials based on cyanoalkylhydrazide and aldehyde groups, the side effects and long-term stability problems of existing vitreous substitutes in clinical applications have been solved, and stable maintenance of intraocular pressure and clear propagation of optical paths have been achieved.

CN119113216BActive Publication Date: 2025-03-18CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411621443.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-18
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

Existing vitreous alternatives such as silicone oil and expandable gases have side effects in clinical applications and are difficult to exist stably for a long time, affecting intraocular pressure and light propagation.

Method used

A cyanoalkylhydrazide and aldehyde group-based injectable hydrogel material was developed to form a C=C double bond crosslinking structure through Knoevenagel condensation reaction, which has injectability and long-term stability.

Benefits of technology

The hydrogel material can exist stably in the vitreous cavity for a long time, maintains stability in the intraocular pressure, provides a clear light path, and can degrade within an appropriate time, without the need for secondary surgical removal, improving the treatment effect and reducing patient pain.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119113216B_ABST
    Figure CN119113216B_ABST
Patent Text Reader

Abstract

The present invention provides a material belonging to the field of material science and technology, and in particular relates to an injectable hydrogel material, a preparation method thereof, and an application as a vitreous substitute, wherein the injectable hydrogel is prepared from a cyanoalkyl hydrazide polymer and a polymer containing an aldehyde functional group. The injectable hydrogel material provided by the present invention is a C=C double-bond cross-linked hydrogel material formed by a Knoevenagel condensation reaction between cyanoacetylhydrazide and an aldehyde group. The preparation conditions are mild, the gelation time is moderate, the material has an injectable property, and the material can be long-term stable after injection, maintain stable intraocular pressure, and support the retina. At the same time, the material can provide advantages such as a clear light path, and can be applied in the medical field of vitreous substitutes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material science, and in particular relates to an injectable hydrogel material, a preparation method thereof and an application thereof as a vitreous substitute. Background Art

[0002] The vitreous is a transparent, gelatinous substance composed of hyaluronic acid (HA) and collagen (type II, V / XI, and IX), which occupies the space between the lens and the retina. The vitreous supports and protects the retina, promotes the diffusion of metabolites, and facilitates the passage of light. With age and accidents, several vision-threatening diseases, including rhegmatogenous retinal detachment (RRD), severe diabetic retinopathy, penetrating ocular trauma, macular holes, and proliferative vitreoretinopathy (PVR), usually require vitrectomy followed by vitreous substitute tamponade to stabilize the retina. The selection of appropriate substitute filling materials after vitrectomy is a current clinical challenge.

[0003] At present, the commonly used vitreous substitutes in clinical practice mainly include silicone oil and expandable gas. Although silicone oil and expandable gas have been proven to be effective filling materials, these filling materials have certain side effects as vitreous substitutes and are not perfect treatment options for patients with eye diseases. After filling with silicone oil, the patient's vision will be blurred and the patient needs to keep his face down for a long time. At the same time, silicone oil will emulsify and cause increased intraocular pressure and inflammation. After a period of filling, additional removal surgery is required, otherwise it will increase the risk of cataracts and glaucoma. The side effects of expandable gas mainly include increased intraocular pressure after surgery, cataract formation, foveal sensitivity and corneal endothelial changes. At the same time, due to the difference in refractive index between the gas and the surrounding eye tissue, temporary visual impairment will also occur. These obvious side effects reduce the therapeutic effect of vitreous substitutes.

[0004] Biomaterials can be synthesized in vitro, and their mechanical and biochemical properties can be customized to fully meet the requirements of vitreous substitutes and achieve the best therapeutic effect. Therefore, the development of new biomaterials with customizable properties is the key to providing the most suitable vitreous substitutes to solve eye disease problems. Among them, injectable hydrogel materials can be injected into the vitreous cavity through minimally invasive injection. After injection, they can adapt to the shape of the injection site, and have good light transmittance, adjustable mechanical properties and biocompatibility, making them ideal vitreous substitutes.

[0005] Injectable hydrogels can be prepared by the following two methods. One is in situ molding: first, two groups that can undergo bioorthogonal chemical reactions (such as Michael addition reaction between thiol and acrylamide double bonds) are used to modify the polymer chains selected in advance or to initiate the polymerization of small molecules containing the above groups to prepare polymers containing the two groups respectively, and the two polymers are prepared into uniform solutions according to the optimal ratio selected, and directly injected into the vitreous cavity through a double-barreled syringe. The hydrogel is quickly formed in situ to achieve the role of vitreous substitute (Ting Wang, Jing Deng, Ruijin Ran, Wenqiang Shi, Yunxia Gao, Xiang Ren, Jun Cao, Ming Zhang, In-situ forming PEG-engineering hydrogels with anti-fouling characteristics as an artificial vitreous body, Chemical Engineering Journal 449 (2022) 137486), but for injectable hydrogels formed in situ, cross-linking reactions occur in the eye, and the biosafety is poor. At the same time, there may be problems with the diffusion of some unreacted small molecules to other parts of the eye, thus causing certain side effects. The other is an injectable hydrogel prepared using dynamic bonds (imide bonds, borate bonds, oxime bonds, etc.) as cross-linking points: first, two polymers containing groups that can undergo dynamic cross-linking reactions are synthesized, and then a uniform solution of the two polymers is prepared according to the optimized best formula, and then the two solutions are mixed in a specific ratio and allowed to stand for a long time to form a dynamic hydrogel. Due to the dynamic nature of the cross-linking points, the hydrogel has the property of shear thinning. After the molding is stable, it can be injected into the vitreous cavity through a syringe and heal in situ, realizing the role of vitreous substitute (Geunho Choi, Seoung Hyun An, Jae-Won Choi, Mee Sook Rho, Woo Chan Park, Woo jin Jeong, Hyung JoonCha, Injectable alginate-based in situ self-healable transparent hydrogel as a vitreous substitute with a tamponading function, Biomaterials 305 (2024)122459). For injectable hydrogels cross-linked with dynamic bonds, due to the rapid exchange kinetics of the dynamic bonds, the stability of the hydrogel itself is poor and cannot provide long-term stability.At the same time, hydrogels tend to swell after their cross-linking density decreases, causing an increase in intraocular pressure.

[0006] How to maintain stability and a constant swelling rate of injectable hydrogels in the vitreous cavity to prevent the imbalance of intraocular pressure caused by excessive expansion is an urgent problem to be solved. Therefore, in view of the above problems, how to develop an injectable hydrogel that has both injectability and stability and can maintain a constant swelling rate, that is, an injectable hydrogel material that can be injected into the vitreous cavity and can exist stably for a long time, maintain normal intraocular pressure, and does not affect the propagation of light is imminent and is one of the problems that many researchers in this field need to solve. Summary of the invention

[0007] In view of this, the technical problem to be solved by the present invention is to provide an injectable hydrogel material having a specific cross-linking structure and capable of maintaining a low swelling rate for a long time, a preparation method thereof and an application thereof as a vitreous substitute.

[0008] The invention provides an injectable hydrogel material, which is formed by a polymer; the polymer comprises a cyanoalkyl hydrazide functionalized polymer and a polymer containing an aldehyde functional group.

[0009] Preferably, the cyanoalkyl hydrazide functionalized polymer comprises a cyanoalkyl hydrazide functionalized polysaccharide polymer and / or a cyanoalkyl hydrazide functionalized multi-arm polyethylene glycol;

[0010] The polymer containing aldehyde functional groups includes aldehyde functionalized polysaccharide and / or aldehyde functionalized multi-arm polyethylene glycol.

[0011] Preferably, the cyanoalkylhydrazide functionalized polymer comprises one or more of cyanoalkylhydrazide functionalized hyaluronic acid, cyanoalkylhydrazide functionalized sodium hyaluronate, cyanoalkylhydrazide functionalized alginate, cyanoalkylhydrazide functionalized sodium alginate, cyanoalkylhydrazide functionalized four-arm polyethylene glycol, cyanoalkylhydrazide functionalized six-arm polyethylene glycol and cyanoalkylhydrazide functionalized eight-arm polyethylene glycol;

[0012] The polymer containing aldehyde functional groups includes one or more of aldehyde functionalized dextran, aldehyde functionalized hyaluronic acid, aldehyde functionalized sodium hyaluronate, aldehyde functionalized four-arm polyethylene glycol, aldehyde functionalized six-arm polyethylene glycol and aldehyde functionalized eight-arm polyethylene glycol;

[0013] The cyanoalkyl hydrazide functionalized polymer is a cyanoacetohydrazide functionalized polymer.

[0014] Preferably, the cyanoalkyl hydrazide functionalized polymer is selected from one or more structures represented by formula (I-1) to formula (I-3):

[0015]

[0016]

[0017]

[0018] m, n, p and q are degrees of polymerization, and m, n, p and q are each independently an integer of 20 to 300; e in formula (I-3) is a repeating unit, and e is an integer of 10 to 100.

[0019] Preferably, the polymer containing an aldehyde functional group is selected from one or more structures represented by formula (II-1) to formula (II-3):

[0020]

[0021]

[0022]

[0023] a, b, c and d are degrees of polymerization, and a, b, c and d are each independently an integer of 20 to 300; in formula (II-3), f is a repeating unit, and f is an integer of 10 to 100.

[0024] Preferably, the mass ratio of the cyanoalkyl hydrazide functionalized polymer to the polymer containing aldehyde functional groups is 1:(0.1-10).

[0025] The present invention also provides a method for preparing the above-mentioned injectable hydrogel material, comprising the following steps:

[0026] S1) providing a cyanoalkyl hydrazide functionalized polymer solution and a polymer solution containing an aldehyde functional group;

[0027] S2) The polymer solution functionalized with cyanoalkyl hydrazide is mixed with the polymer solution containing aldehyde functional groups to undergo a cross-linking reaction to obtain an injectable hydrogel material.

[0028] Preferably, the concentration of the cyanoalkyl hydrazide functionalized polymer in the cyanoalkyl hydrazide functionalized polymer solution is 5 to 100 mg / mL;

[0029] The concentration of the polymer containing aldehyde functional groups in the polymer solution containing aldehyde functional groups is 50-150 mg / mL;

[0030] The solvents in the cyanoalkyl hydrazide functionalized polymer solution and the polymer solution containing aldehyde functional groups are independently selected from one or more of water, physiological saline and buffer solution.

[0031] Preferably, the mixing temperature is 4°C to 37°C; the cross-linking reaction temperature is 4°C to 37°C; and the cross-linking reaction time is 5 to 20 min.

[0032] The present invention also provides a use of the injectable hydrogel as a vitreous substitute.

[0033] The present invention provides an injectable hydrogel material, which is formed by a polymer; the polymer includes a cyanoalkyl hydrazide functionalized polymer and a polymer containing an aldehyde functional group. Compared with the prior art, the injectable hydrogel material provided by the present invention is a C=C double bond cross-linked hydrogel material formed by a Knoevenagel condensation reaction between cyanoacetylhydrazide and an aldehyde group. It has mild preparation conditions, moderate gelation time, injectable properties, and can be long-term stable after injection, maintain stable intraocular pressure, and can support the retina, provide a clear light path, and can be applied in the field of vitreous replacement medicine. Compared with current clinical methods, the injectable hydrogel material provided in the present invention can provide a clear light path immediately after surgery, does not need to maintain a face-down posture for a long time, and can be degraded within a suitable time without the need for secondary surgery to remove, thereby improving the treatment effect and alleviating the patient's postoperative pain.

[0034] The experimental results show that the injectable hydrogel prepared by the present invention has a suitable gelation time and mechanical strength, presents a regular porous network structure inside, has an injectable property, can maintain a stable swelling rate, and has good light transmittance and can exist stably for a long time. The biocompatibility of the hydrogel is good. Therefore, it can be used as an injectable hydrogel material for vitreous replacement. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 HA-CAH prepared in Example 1 of the present invention 40 H NMR spectrum of

[0036] Figure 2 HA-CAH prepared in Example 1 of the present invention 40 Fourier infrared image;

[0037] Figure 3 This is the hydrogen nuclear magnetic resonance spectrum of o-Dex prepared in Example 6 of the present invention;

[0038] Figure 4 This is the Fourier infrared image of o-Dex prepared in Example 6 of the present invention;

[0039] Figure 5It is a diagram of the storage modulus and loss modulus of the hydrogels of Example 13, Example 15, Example 19, Example 21, Example 23 and Example 25 of the present invention;

[0040] Figure 6 This is a shear thinning performance curve of the hydrogel prepared in Example 32 of the present invention;

[0041] Figure 7 This is a UV-visible spectrum of the hydrogel prepared in Example 23 of the present invention;

[0042] Figure 8 This is a scanning electron microscope (SEM) image of the hydrogel prepared in Example 40 of the present invention;

[0043] Fig. 9 The swelling and degradation diagrams of the hydrogels prepared in Examples 12 and 14 of the present invention;

[0044] Fig.10 The present invention provides a graph showing the cytotoxicity of an injectable hydrogel material to retinal pigment epithelial cells (RPE cells). DETAILED DESCRIPTION

[0045] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0046] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0047] There is no particular limitation on the purity of all raw materials in the present invention. The present invention preferably uses analytically pure raw materials or raw materials that meet the purity standards related to the preparation of vitreous substitute materials.

[0048] The sources and abbreviations of all raw materials in the present invention are conventional sources and abbreviations in the field, and are clear and definite in the field of their relevant uses. Those skilled in the art can purchase them from commercial sources or prepare them by conventional methods based on the abbreviations and corresponding uses.

[0049] In particular, the present invention involves many new structures or substituent groups. Therefore, the present invention names the above structures and groups in accordance with the naming principles well known in the art, and those skilled in the art can clearly and clearly know the meaning of the present invention based on the common sense in the art. Among them, due to the difference in naming principles, the names of some structures and substituent groups may not be unique. In the present invention, references can also be made based on reaction mechanisms, reaction routes and specific structural formulas.

[0050] The invention provides an injectable hydrogel material, which is formed by a polymer; the polymer comprises a cyanoalkyl hydrazide functionalized polymer and a polymer containing an aldehyde functional group.

[0051] The injectable hydrogel material provided by the present invention has a shear-thinning property and can remain stable without hydrolysis after injection. At the same time, the hydrogel can maintain a constant swelling rate, good light transmittance and good biocompatibility, and can be used as an injectable hydrogel material for vitreous replacement.

[0052] According to the present invention, the cyanoalkyl hydrazide functionalized polymer is preferably a cyanoalkyl hydrazide functionalized polymer including a cyanoalkyl hydrazide functionalized polysaccharide polymer and / or a cyanoalkyl hydrazide functionalized multi-arm polyethylene glycol, more preferably including one or more of cyanoalkyl hydrazide functionalized hyaluronic acid, cyanoalkyl hydrazide functionalized sodium hyaluronate, cyanoalkyl hydrazide functionalized alginate, cyanoalkyl hydrazide functionalized sodium alginate, cyanoalkyl hydrazide functionalized four-arm polyethylene glycol, cyanoalkyl hydrazide functionalized six-arm polyethylene glycol and cyanoalkyl hydrazide functionalized eight-arm polyethylene glycol.

[0053] According to the present invention, the carbon number of the alkyl hydrazide in the cyanoalkyl hydrazide functionalized polymer is preferably 1 to 10, more preferably 1 to 6, further preferably 2 to 4, further preferably 2 to 3; specifically, the cyanoalkyl hydrazide functionalized polymer is a cyanoacetohydrazide functionalized polymer.

[0054] According to the present invention, the grafting rate of the cyanoalkyl hydrazide functionalized polymer cyanoalkyl hydrazide is preferably 2.5% to 60%, more preferably 5% to 50%, and even more preferably 10% to 40%.

[0055] In a specific embodiment provided by the present invention, the cyanoalkyl hydrazide functionalized polymer is preferably one or more structures represented by formula (I-1) to formula (I-3):

[0056]

[0057]

[0058]

[0059] m, n, p and q are the degrees of polymerization, and m, n, p and q are each independently preferably an integer of 20 to 300, more preferably an integer of 50 to 250, further preferably an integer of 50 to 200, further preferably an integer of 70 to 150, and most preferably an integer of 100 to 120; in formula (I-3), e is a repeating unit, and e is preferably an integer of 10 to 100, more preferably an integer of 20 to 90, further preferably an integer of 30 to 80, and most preferably an integer of 40 to 60.

[0060] According to the present invention, the polymer containing aldehyde functional groups preferably includes aldehyde functionalized polysaccharides and / or aldehyde functionalized multi-arm polyethylene glycol, and more preferably includes one or more of aldehyde functionalized dextran, aldehyde functionalized hyaluronic acid, aldehyde functionalized sodium hyaluronate, aldehyde functionalized four-arm polyethylene glycol, aldehyde functionalized six-arm polyethylene glycol and aldehyde functionalized eight-arm polyethylene glycol; the aldehyde functionalized multi-arm polyethylene glycol is preferably an aldehyde functionalized multi-arm polyethylene glycol containing phenyl groups.

[0061] In a specific embodiment provided by the present invention, the polymer containing an aldehyde functional group is preferably one or more structures represented by formula (II-1) to formula (II-3):

[0062]

[0063]

[0064]

[0065] a, b, c and d are the degrees of polymerization, and a, b, c and d are each independently preferably an integer of 20 to 300, more preferably an integer of 50 to 250, further preferably an integer of 50 to 200, further preferably an integer of 70 to 150, and most preferably an integer of 100 to 120; in formula (II-3), f is a repeating unit, and f is preferably an integer of 10 to 100, more preferably an integer of 20 to 90, further preferably an integer of 30 to 80, and most preferably an integer of 40 to 60.

[0066] According to the present invention, the mass ratio of the cyanoalkyl hydrazide functionalized polymer to the polymer containing aldehyde functional groups is preferably 1:(0.1-10), more preferably 1:(0.15-8), more preferably 1:(0.2-6), more preferably 1:(0.2-5), and most preferably 1:(0.25-4); in some embodiments provided by the present invention, the mass ratio of the cyanoalkyl hydrazide functionalized polymer to the polymer containing aldehyde functional groups is specifically 1:0.25, 1:0.5, 1:1 or 1:4.

[0067] According to the present invention, a cyanoalkyl hydrazide functionalized polymer reacts with an aldehyde functional group-containing polymer via a Knoevenagel condensation reaction, preferably forming a cross-linked structure of C=C double bonds to form an injectable hydrogel material.

[0068] According to the present invention, the injectable hydrogel material is optically transparent; specifically, the transmittance of the injectable hydrogel is above 90% in the range of 400-800 nm.

[0069] According to the present invention, the injectable hydrogel material has a refractive index close to that of natural vitreous.

[0070] According to the present invention, the injectable hydrogel material can exist stably for a long time.

[0071] In the present invention, the injectable hydrogel material refers to the material that can be injected.

[0072] In the present invention, the injectable use refers to the injectable use after the hydrogel is stabilized.

[0073] The injectable hydrogel material provided by the present invention is a C=C double bond cross-linked hydrogel material formed by the Knoevenagel condensation reaction of cyanoacetylhydrazine and aldehyde groups. The preparation conditions are mild, the gelation time is moderate, the material has injectable properties, and the material can be long-term stable after injection, maintains stable intraocular pressure, and can support the retina, provide a clear light path, and can be applied in the medical field of vitreous replacement. Compared with the current clinical means, the injectable hydrogel material provided in the present invention can provide a clear light path immediately after surgery, does not need to maintain a face-down posture for a long time, and can be degraded within a suitable time without the need for secondary surgery to remove the material, thereby improving the treatment effect and alleviating the postoperative pain of the patient.

[0074] The present invention also provides a method for preparing the above-mentioned injectable hydrogel material, comprising the following steps: S1) providing a cyanoalkyl hydrazide functionalized polymer solution and a polymer solution containing an aldehyde functional group; S2) mixing the cyanoalkyl hydrazide functionalized polymer solution and the polymer solution containing an aldehyde functional group to perform a cross-linking reaction to obtain an injectable hydrogel material.

[0075] The present invention has no special restrictions on the sources of all raw materials, and any raw materials available on the market can be used. The cyanoalkyl hydrazide functionalized polymer and the polymer containing aldehyde functional group are the same as described above, and will not be described in detail here.

[0076] In a specific embodiment provided by the present invention, the cyanoalkyl hydrazide functionalized polymer is preferably prepared according to the following steps: a polymer containing a carboxyl group, a cyanoalkyl hydrazide, a condensation agent and an activator are mixed in a solvent for condensation reaction to obtain a cyanoalkyl hydrazide functionalized polymer; the polymer containing a carboxyl group is preferably a polysaccharide polymer, more preferably one or more of hyaluronic acid, sodium hyaluronate, alginic acid and sodium alginate; the number average molecular weight of the polysaccharide polymer is preferably 10000~300000 g / mol, more preferably 25000~250000 g / mol, more preferably 25000~200000 g / mol, more preferably 35000~150000 g / mol, more preferably 50000~150000 g / mol, most preferably 70000~110000 g / mol. g / mol; the carbon number of the alkyl group in the cyanoalkyl hydrazide is preferably 1-10, more preferably 1-6, more preferably 2-4, and more preferably 2-3; in the present invention, specifically, the cyanoalkyl hydrazide is cyanoacetic hydrazide; the mass ratio of the polymer containing a carboxyl group to the cyanoalkyl hydrazide is preferably 2:(0.01-0.5), more preferably 2:(0.01-0.3), more preferably 2:(0.01-0.2), more preferably 2:(0.02-0.15), and most preferably 2:(0.025-0.1); in some embodiments provided by the present invention, the mass ratio of the polymer containing a carboxyl group to the cyanoalkyl hydrazide is specifically 2:0.1, 2:0.05 or 2:0.025; the condensing agent is preferably a carbodiimide series condensing agent, such as N, N'-dicyclohexylcarbodiimide (DCC), N, N'-diisopropylcarbodiimide (DIC) and 1-ethyl-(3 -dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl); the activator is a carboxyl activator well known to those skilled in the art, without special restrictions, and is preferably N-hydroxysuccinimide (NHS) in the present invention; the solvent is preferably one or more of water, dimethyl sulfoxide and N,N-dimethylformamide; the condensation reaction is preferably carried out at room temperature; the condensation reaction time is preferably 1 to 3 days, more preferably 1.5 to 2.5 days, and more preferably 2 days; after the condensation reaction is completed, it is preferably dialyzed in deionized water and freeze-dried to obtain a cyanoalkyl hydrazide functionalized polymer; the dialysis time is preferably 60 to 84 hours, more preferably 66 to 79 hours, and more preferably 72 hours.

[0077] In another specific embodiment provided by the present invention, the cyanoalkyl hydrazide functionalized polymer is preferably prepared according to the following steps: reacting a polymer containing a hydroxyl group, an activator and a cyanoalkyl hydrazide in an organic solvent to obtain a cyanoalkyl hydrazide functionalized polymer; the polymer containing a hydroxyl group is preferably a multi-arm polyethylene glycol, more preferably one or more of a four-arm polyethylene glycol, a six-arm polyethylene glycol and an eight-arm polyethylene glycol; the polymer containing a hydroxyl group is preferably 2000-20000 g / mol, more preferably 5000-18000 g / mol, more preferably 6000-15000 g / mol, more preferably 8000-12000 g / mol, and most preferably 10000 g / mol; the activator is preferably N, N′-carbonyldiimidazole (CDI); the cyanoalkyl hydrazide is the same as described above and will not be repeated here; the mass ratio of the polymer containing hydroxyl groups to cyanoalkyl hydrazide is preferably 5: (0.5~2), more preferably 5: (0.8~1.5), and more preferably 5: 1; the organic solvent is an organic solvent well known to those skilled in the art, and there is no special limitation. In the present invention, it is preferably one or more of dichloromethane, dimethyl sulfoxide, tetrahydrofuran, and N, N-dimethylformamide; in the present invention, it is preferred to firstly mix the polymer containing hydroxyl groups with the activator in an organic solvent for reaction, and then mix with cyanoalkyl hydrazide for reaction to obtain a cyanoalkyl hydrazide functionalized polymer.

[0078] In a specific embodiment provided by the present invention, the polymer containing aldehyde functional groups is prepared according to the following method: a polymer containing vicinal dihydroxyl groups is oxidized by sodium periodate to obtain a polymer containing aldehyde functional groups; the polymer containing vicinal dihydroxyl groups is preferably a polysaccharide polymer, more preferably one or more of dextran, hyaluronic acid and sodium hyaluronate; the number average molecular weight of the polysaccharide polymer is preferably 10000-300000 g / mol, more preferably 25000-250000 g / mol, more preferably 25000-200000 g / mol, more preferably 35000-150000 g / mol, more preferably 50000-150000 g / mol, most preferably 70000-110000 g / mol. g / mol; the oxidation is preferably carried out in a solvent; the solvent is preferably one or more of water, dimethyl sulfoxide and N,N-dimethylformamide; the mass ratio of the polymer containing o-dihydroxy group to sodium periodate is preferably 2:(0.1-1), more preferably 2:(0.3-0.8), more preferably 2:(0.4-0.6), and most preferably 2:0.5; the oxidation time is preferably 2-6 h, more preferably 3-5 h, and more preferably 4 h; after the oxidation is completed, ethylene glycol is preferably added to terminate the reaction, and the reaction solution is dialyzed in deionized water and freeze-dried to obtain a polymer containing aldehyde functional groups; the dialysis time is preferably 60-84 h, more preferably 66-79 h, and more preferably 72 h.

[0079] In another specific embodiment provided by the present invention, the polymer containing aldehyde functional groups is prepared according to the following method: a polymer containing hydroxyl groups, alkanoylbenzoic acid, an acylation catalyst and a condensation agent are reacted in a solvent to obtain a polymer containing aldehyde functional groups; the polymer containing hydroxyl groups is preferably multi-arm polyethylene glycol, more preferably one or more of four-arm polyethylene glycol, six-arm polyethylene glycol and eight-arm polyethylene glycol; the polymer containing hydroxyl groups is preferably 2000~20000 g / mol, more preferably 5000~18000 g / mol, more preferably 6000~15000 g / mol, more preferably 8000~12000 g / mol, and most preferably 10000 g / mol; the alkanoylbenzoic acid is preferably p-formylbenzoic acid; the acylation catalyst is preferably dimethylaminopyridine (DMAP); the condensing agent is preferably a carbodiimide series condensing agent, such as N, N'-dicyclohexylcarbodiimide (DCC), N, N'-diisopropylcarbodiimide (DIC) and 1-ethyl-(3 -dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl); the solvent is preferably one or more of dichloromethane, dimethyl sulfoxide and water; the mass ratio of the polymer containing hydroxyl groups to alkanoylbenzoic acid is preferably 5: (0.01-0.2), more preferably 5: (0.03-0.1), more preferably 5: (0.04-0.08), and most preferably 5: 0.06; the reaction temperature is preferably 20°C-30°C, more preferably 25°C; the reaction time is preferably 1-3 days, more preferably 2 days; after the reaction is completed, preferably washing with cold saturated sodium chloride solution and cold saturated sodium bicarbonate solution in sequence, collecting the organic phase, concentrating and then precipitating with cold ether to obtain a solid primary product, and then the solid primary product is dialyzed and purified in deionized water and freeze-dried to obtain a polymer containing aldehyde functional groups.

[0080] According to the present invention, the concentration of the cyanoalkyl hydrazide functionalized polymer in the cyanoalkyl hydrazide functionalized polymer solution is preferably 5-100 mg / mL, more preferably 10-90 mg / mL, further preferably 20-80 mg / mL, and most preferably 40-60 mg / mL.

[0081] According to the present invention, the cyanoalkyl hydrazide functionalized polymer solution is prepared according to the following method: a cyanoalkyl hydrazide functionalized polymer is mixed with an aqueous solvent to obtain a cyanoalkyl hydrazide functionalized polymer solution; the aqueous solvent can be an aqueous solvent well known to those skilled in the art, and there is no special restriction. In the present invention, it is preferably one or more of water, physiological saline and buffer solution; the mixing temperature is preferably 4°C to 37°C, more preferably 6°C to 35°C, more preferably 8°C to 32°C, more preferably 12°C to 28°C, more preferably 16°C to 24°C, and more preferably 19°C to 21°C.

[0082] According to the present invention, the concentration of the polymer containing aldehyde functional groups in the polymer solution containing aldehyde functional groups is preferably 50-150 mg / mL, more preferably 60-120 mg / mL, further preferably 80-110 mg / mL, and most preferably 90-100 mg / mL.

[0083] According to the present invention, the polymer solution containing aldehyde functional groups is prepared according to the following method: a polymer containing aldehyde functional groups is mixed with an aqueous solvent to obtain a polymer solution containing aldehyde functional groups; the aqueous solvent can be an aqueous solvent well known to those skilled in the art, and there is no special restriction. In the present invention, it is preferably one or more of water, physiological saline and buffer solution; the mixing temperature is preferably 4°C to 37°C, more preferably 6°C to 35°C, more preferably 8°C to 32°C, more preferably 12°C to 28°C, more preferably 16°C to 24°C, and more preferably 19°C to 21°C.

[0084] The polymer solution functionalized with cyanoalkyl hydrazide is mixed with the polymer solution containing aldehyde functional groups for cross-linking reaction to obtain an injectable hydrogel material; the mass ratio of the cyanoalkyl hydrazide functionalized polymer in the cyanoalkyl hydrazide functionalized polymer solution to the polymer containing aldehyde functional groups in the polymer solution containing aldehyde functional groups is preferably 1:(0.1-10), more preferably 1:(0.15-8), more preferably 1:(0.2-6), more preferably 1:(0.2-5), and most preferably 1:( 0.25~4); the mixing temperature is preferably 4°C~37°C, more preferably 6°C~35°C, more preferably 8°C~32°C, more preferably 12°C~28°C, more preferably 16°C~24°C, more preferably 19°C~21°C; the cross-linking reaction temperature is preferably 4°C~37°C, more preferably 6°C~35°C, more preferably 8°C~32°C, more preferably 12°C~28°C, more preferably 16°C~24°C, more preferably 19°C~21°C; the cross-linking reaction time is preferably 5~20 min, more preferably 6~18 min, more preferably 8~15 min, more preferably 8~12 min, and most preferably 8~10 min.

[0085] The present invention dissolves a cyanoacetylhydrazine functionalized polymer and a polymer containing an aldehyde functional group in an aqueous solvent to obtain a uniform solution; the obtained cyanoacetylhydrazine functionalized polymer and the solution of the polymer containing an aldehyde functional group are uniformly mixed, and a cross-linking polymerization reaction is performed to obtain an injectable hydrogel material. The injectable hydrogel material provided by the present invention has a specific cross-linking structure, which can not only be injected into the vitreous cavity by minimally invasive injection, but also can maintain long-term stability and non-degradation after injection into the vitreous cavity. At the same time, through formula optimization, the hydrogel can maintain a low swelling rate for a long time to maintain stable intraocular pressure. At the same time, the preparation method is simple, the conditions are mild, and it is more suitable for large-scale promotion and application as a vitreous substitute in eye surgery.

[0086] The present invention also provides a use of the injectable hydrogel as a vitreous substitute.

[0087] The injectable hydrogel material provided by the present invention has a specific structure and is used as a vitreous substitute. It can not only be injected into the vitreous cavity by minimally invasive injection, but also can be stable for a long time after injection, maintain stable intraocular pressure, and can also support the retina and provide a clear light path, which is suitable as a vitreous substitute. At the same time, the preparation method is simple, the conditions are mild, and it is more suitable for large-scale promotion and application.

[0088] To further illustrate the present invention, an injectable hydrogel material provided by the present invention, a preparation method thereof and an application thereof as a vitreous substitute are described in detail below in conjunction with embodiments.

[0089] The reagents used in the following examples are all commercially available; the number average molecular weight of the sodium hyaluronate used in the examples is 100,000 g / mol; the number average molecular weight of the sodium alginate is 100,000 g / mol, the number average molecular weight of the four-arm polyethylene glycol is 10,000 g / mol; and the number average molecular weight of the dextran is 70,000 g / mol.

[0090] Example 1

[0091] 2 g of sodium hyaluronate (HA) was dissolved in 200 mL (pH: 5-6) of deionized water. After HA was completely dissolved, 0.7 g of N-hydroxysuccinimide (NHS), 1.4 g of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl) and 0.1 g of cyanoacethydrazide (CAH) were added to the reaction solution in sequence. After reacting at room temperature for 2 days, the reaction solution was directly dialyzed in deionized water for 72 hours and freeze-dried to obtain a cyanoacethydrazide functionalized powdered polymer product (HA-CAH) having the structure shown in Formula I-1. 40 ).

[0092] The HA-CAH obtained above was characterized by nuclear magnetic resonance analysis and Fourier transform infrared spectroscopy analysis; see Figure 1 , Figure 1 HA-CAH prepared in Example 1 of the present invention 40 Perform H NMR spectroscopy; see Figure 2 , Figure 2 HA-CAH prepared in Example 1 of the present invention 40 Perform Fourier transform infrared spectroscopy.

[0093] Example 2

[0094] 2 g of sodium hyaluronate (HA) was dissolved in 200 mL (pH: 5-6) of deionized water. After HA was completely dissolved, 0.7 g of N-hydroxysuccinimide (NHS), 1.4 g of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl) and 0.05 g of cyanoacethydrazide (CAH) were added to the reaction solution in sequence. After reacting at room temperature for 2 days, the reaction solution was directly dialyzed in deionized water for 72 hours and freeze-dried to obtain a cyanoacethydrazide functionalized powdered polymer product (HA-CAH) having the structure shown in Formula I-1. 20 ).

[0095] Example 3

[0096] 2 g of sodium hyaluronate (HA) was dissolved in 200 mL (pH: 5-6) of deionized water. After HA was completely dissolved, 0.7 g of N-hydroxysuccinimide (NHS), 1.4 g of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl) and 0.025 g of cyanoacetylhydrazine (CAH) were added to the reaction solution in sequence. After reacting at room temperature for 2 days, the reaction solution was directly dialyzed in deionized water for 72 hours and freeze-dried to obtain a cyanoacetylhydrazine functionalized powdered polymer product (HA-CAH) having the structure shown in Formula I-1. 10 ).

[0097] Example 4

[0098] 2 g of sodium alginate (SA) was dissolved in 200 mL (pH: 5-6) of deionized water. After SA was completely dissolved, 0.7 g of N-hydroxysuccinimide (NHS), 1.4 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl) and 0.1 g of cyanoacethydrazide (CAH) were added to the reaction solution in sequence. After reacting at room temperature for 2 days, the reaction solution was directly dialyzed in deionized water for 72 hours and freeze-dried to obtain a cyanoacethydrazide functionalized powdered polymer product (SA-CAH) having the structure shown in Formula I-2.

[0099] Example 5

[0100] 3 g of N, N-carbonyldiimidazole (CDI) was dissolved in 20 mL of dichloromethane to obtain a CDI solution; 5 g of four-arm polyethylene glycol was dissolved in 20 mL of dichloromethane to obtain a four-arm polyethylene glycol solution; the four-arm polyethylene glycol solution was then added dropwise to the CDI solution to react for four hours, and the lower organic phase was obtained after multiple water washings. The solvent was spin-dried to obtain CDI-modified 4-arm PEG, and then 5 g of CDI-modified 4-arm PEG and 1 g of cyanoacethydrazide were co-dissolved in 50 mL of N, N-dimethylformamide to react for 4 hours. The reaction solution was dialyzed in deionized water for 72 hours, and freeze-dried to obtain a cyanoacethydrazide functionalized powdered polymer product (4-arm PEG-CAH) having a structure shown in Formula I.

[0101] Example 6

[0102] 2 g of dextran (Dex) was dissolved in 200 mL (pH: 5~6) deionized water to obtain a dextran solution; 0.5 g of sodium periodate was dissolved in 50 mL of deionized water and then added dropwise to the dextran solution. After reacting at room temperature for 4 hours, 20 mL of ethylene glycol solution was added to terminate the reaction. The reaction solution was then dialyzed in deionized water for 72 hours and freeze-dried to obtain an aldehyde-containing flocculent polymer product (o-Dex) having a structure shown in Formula II-1.

[0103] The o-Dex obtained above was characterized by nuclear magnetic resonance analysis and Fourier transform infrared spectroscopy analysis; see Figure 3 , Figure 3 The o-Dex prepared in Example 6 of the present invention was subjected to a hydrogen nuclear magnetic resonance spectrum. Figure 4 , Figure 4 Fourier transform infrared spectrum of o-Dex prepared in Example 6 of the present invention.

[0104] Example 7

[0105] Dissolve 2 g of sodium hyaluronate (HA) in 200 mL (pH: 5~6) deionized water to obtain a sodium hyaluronate solution; dissolve 0.5 g of sodium periodate in 50 mL of deionized water and add the mixture dropwise to the sodium hyaluronate solution. After reacting at room temperature for 4 hours, add 20 mL of ethylene glycol solution to terminate the reaction. The reaction solution is then dialyzed in deionized water for 72 hours and freeze-dried to obtain an aldehyde-containing flocculent polymer product (o-HA) having a structure shown in Formula II-2.

[0106] Example 8

[0107] 5 g of four-arm polyethylene glycol (4-arm PEG), 0.06 g of dimethylaminopyridine (DMAP) and 1.5 g of 4-formylbenzoic acid were dissolved in 100 mL of anhydrous dichloromethane, and then 2 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride was added to the reaction solution. After reacting at 25 degrees Celsius for 2 days, the reaction solution was washed 3 times with a cold saturated sodium chloride solution, 50 mL each time. Then, it was washed 3 times with a cold saturated sodium bicarbonate solution, 50 mL each time. After washing, the lower organic phase was collected, an appropriate amount of anhydrous magnesium sulfate was added thereto and dried for 12 hours, and then filtered to obtain a filtrate. The filtrate was concentrated by rotary evaporation and precipitated in cold ether several times, and a solid initial product was obtained by filtration. It was then dialyzed in deionized water for 72 hours and freeze-dried to obtain a powdered product (4-arm PEG-FA) containing benzaldehyde having the structure shown in formula II-3.

[0108] Example 9

[0109] The HA-CAH prepared in Example 1 40 (100 mg) was dissolved in 2 mL PBS to obtain solution 1; o-Dex (100 mg) prepared in Example 6 was dissolved in 1 mL PBS to obtain solution 2; Solution 1 (200 μL) and solution 2 (100 μL) were fully stirred and allowed to gel at room temperature for 10 min.

[0110] Example 10

[0111] The HA-CAH prepared in Example 1 40 (100 mg) was dissolved in 2 mL PBS to obtain solution 3; o-Dex (100 mg) prepared in Example 6 was dissolved in 1 mL PBS to obtain solution 4; Solution 3 (200 μL) and solution 4 (400 μL) were fully stirred and allowed to gel at room temperature for 5 min.

[0112] Embodiment 11

[0113] The HA-CAH prepared in Example 1 40 (100 mg) was dissolved in 2 mL PBS to obtain solution 5; o-Dex (100 mg) prepared in Example 6 was dissolved in 1 mL PBS to obtain solution 6; Solution 5 (200 μL) and solution 6 (25 μL) were fully stirred and allowed to gel at room temperature for 20 min.

[0114] Example 12

[0115] The HA-CAH prepared in Example 1 40(100 mg) was dissolved in 5 mL PBS to obtain solution 7; o-Dex (100 mg) prepared in Example 6 was dissolved in 1 mL PBS to obtain solution 8. Solution 7 (200 μL) and solution 8 (40 μL) were fully stirred and allowed to gel at room temperature for 15 min.

[0116] Example 13

[0117] The solution 7 (200 μL) and solution 8 (40 μL) obtained in Example 12 were fully stirred to obtain a mixed solution, and after the polymerization reaction was completely completed and gelled, the mixed solution was transferred to a rotational rheometer to characterize its storage modulus and loss modulus. The storage modulus was about 100 Pa.

[0118] Embodiment 14

[0119] The HA-CAH prepared in Example 1 40 (100 mg) was dissolved in 10 mL PBS to obtain solution 9; o-Dex (100 mg) prepared in Example 6 was dissolved in 1 mL PBS to obtain solution 10; Solution 9 (200 μL) and solution 10 (20 μL) were fully stirred and allowed to gel at room temperature for 20 min.

[0120] Embodiment 15

[0121] The solution 9 (200 μL) and solution 10 (20 μL) obtained in Example 14 were fully stirred to obtain a mixed solution, and after complete polymerization reaction to form gel, the mixed solution was transferred to a rotational rheometer to characterize its storage modulus and loss modulus. The storage modulus was about 20 Pa.

[0122] Example 16

[0123] The HA-CAH prepared in Example 1 40 (100 mg) was dissolved in 2 mL PBS to obtain solution 11; o-HA (100 mg) prepared in Example 7 was dissolved in 1 mL PBS to obtain solution 12; solution 11 (200 μL) and solution 12 (100 μL) were fully stirred and allowed to gel at room temperature for 6 min.

[0124] Embodiment 17

[0125] The HA-CAH prepared in Example 1 40(100 mg) was dissolved in 2 mL PBS to obtain solution 13; 4-arm PEG-FA (100 mg) prepared in Example 8 was dissolved in 1 mL PBS to obtain solution 14; solution 13 (200 μL) and solution 14 (100 μL) were fully stirred and allowed to gel at room temperature for 7 min.

[0126] Embodiment 18

[0127] The HA-CAH prepared in Example 2 20 (100 mg) was dissolved in 5 mL PBS to obtain solution 15; o-Dex (100 mg) prepared in Example 6 was dissolved in 1 mL PBS to obtain solution 16; Solution 15 (200 μL) and solution 16 (40 μL) were fully stirred and allowed to gel at room temperature for 15 min.

[0128] Embodiment 19

[0129] The solution 15 (200 μL) and solution 16 (40 μL) obtained in Example 18 were fully stirred to obtain a mixed solution, and after the polymerization reaction was completely completed and gelled, the mixed solution was transferred to a rotational rheometer to characterize its storage modulus and loss modulus. The storage modulus was about 100 Pa. Example 20

[0130] The HA-CAH prepared in Example 2 20 (100 mg) was dissolved in 10 mL PBS to obtain solution 17; o-Dex (100 mg) prepared in Example 6 was dissolved in 1 mL PBS to obtain solution 18; solution 17 (200 μL) and solution 18 (20 μL) were fully stirred and allowed to gel at room temperature for 12 min.

[0131] Embodiment 21

[0132] The solution 17 (200 μL) and solution 18 (20 μL) obtained in Example 20 were fully stirred to obtain a mixed solution, and after complete polymerization reaction to form a gel, the solution was transferred to a rotational rheometer to characterize its storage modulus and loss modulus. The storage modulus was about 20 Pa.

[0133] Embodiment 22

[0134] The HA-CAH prepared in Example 3 10(100 mg) was dissolved in 5 mL PBS to obtain solution 19; o-Dex (100 mg) prepared in Example 6 was dissolved in 1 mL PBS to obtain solution 20; Solution 19 (200 μL) and solution 20 (40 μL) were fully stirred and allowed to gel at room temperature for 16 min.

[0135] Embodiment 23

[0136] The solution 19 (200 μL) and solution 20 (40 μL) obtained in Example 22 were fully stirred to obtain a mixed solution, and after the polymerization reaction was completely completed and gelled, the mixed solution was transferred to a rotational rheometer to characterize its storage modulus and loss modulus. The storage modulus was about 100 Pa.

[0137] Embodiment 24

[0138] The HA-CAH prepared in Example 2 10 (100 mg) was dissolved in 10 mL PBS to obtain solution 21; o-Dex (100 mg) prepared in Example 6 was dissolved in 1 mL PBS to obtain solution 22; Solution 21 (200 μL) and solution 22 (20 μL) were fully stirred and allowed to gel at room temperature for 20 min.

[0139] Embodiment 25

[0140] The solution 21 (200 μL) and solution 22 (20 μL) obtained in Example 24 were fully stirred to obtain a mixed solution, and after complete polymerization reaction to form gel, the solution was transferred to a rotational rheometer to characterize its storage modulus and loss modulus. The storage modulus was about 10 Pa.

[0141] See also Figure 5 , Figure 5 These are the storage modulus and loss modulus of the hydrogels obtained in Examples 13, 15, 19, 21, 23 and 25 of the present invention.

[0142] The results are as follows Figure 5 As shown, the storage modulus of the hydrogel is around 100 Pa / 20 Pa, respectively, which is similar to the strength of natural vitreous.

[0143] Embodiment 26

[0144] The SA-CAH (100 mg) prepared in Example 4 was dissolved in 5 mL PBS to obtain solution 23; the o-Dex (100 mg) prepared in Example 6 was dissolved in 1 mL PBS to obtain solution 24; solution 23 (200 μL) and solution 24 (40 μL) were fully stirred and allowed to gel at room temperature for 16 min.

[0145] Embodiment 27

[0146] The SA-CAH (100 mg) prepared in Example 4 was dissolved in 5 mL PBS to obtain solution 25; the o-HA (100 mg) prepared in Example 7 was dissolved in 1 mL PBS to obtain solution 26; solution 25 (200 μL) and solution 26 (40 μL) were fully stirred and allowed to gel at room temperature for 16 min.

[0147] Embodiment 28

[0148] The SA-CAH (100 mg) prepared in Example 4 was dissolved in 5 mL PBS to obtain solution 27; the 4-arm PEG-FA (100 mg) prepared in Example 8 was dissolved in 1 mL PBS to obtain solution 28; solution 27 (200 μL) and solution 28 (40 μL) were fully stirred and allowed to gel at room temperature for 10 min.

[0149] Embodiment 29

[0150] The 4-arm PEG-CAH (100 mg) prepared in Example 5 was dissolved in 1 mL PBS to obtain solution 29; the o-Dex (100 mg) prepared in Example 6 was dissolved in 1 mL PBS to obtain solution 30; solution 29 (200 μL) and solution 30 (200 μL) were fully stirred and allowed to gel at room temperature for 12 min.

[0151] Embodiment 30

[0152] The 4-arm PEG-CAH (100 mg) prepared in Example 5 was dissolved in 1 mL PBS to obtain solution 31; the o-HA (100 mg) prepared in Example 7 was dissolved in 1 mL PBS to obtain solution 32; solution 31 (200 μL) and solution 32 (200 μL) were fully stirred and allowed to gel at room temperature for 12 min.

[0153] Embodiment 31

[0154] The 4-arm PEG-CAH (100 mg) prepared in Example 5 was dissolved in 1 mL PBS to obtain solution 33; the 4-arm PEG-FA (100 mg) prepared in Example 8 was dissolved in 1 mL PBS to obtain solution 34; solution 33 (200 μL) and solution 34 (200 μL) were fully stirred and allowed to gel at room temperature for 8 min.

[0155] Embodiment 32

[0156] The solution 9 (200 μL) and solution 10 (20 μL) obtained in Example 14 were fully stirred to obtain a mixed solution. After the polymerization reaction was completed to form a hydrogel, 1 mL of PBS was added. After reaching swelling equilibrium, the mixture was transferred to a rotational rheometer and the shear thinning properties of the hydrogel were tested by shear rate scanning.

[0157] See also Figure 6 , Figure 6 This is a shear thinning performance curve of the hydrogel prepared in Example 32 of the present invention.

[0158] The results are as follows Figure 6 As shown, after the hydrogel reaches swelling equilibrium, the viscosity of the hydrogel gradually decreases with the increase of shear rate, indicating that the hydrogel has good injectability.

[0159] Embodiment 33

[0160] The hydrogel material obtained in Example 16 was added with 1 mL of PBS to reach swelling equilibrium, and then transferred to a rotational rheometer. The shear rate sweep test proved that the hydrogel had shear thinning properties and good injectability.

[0161] Embodiment 34

[0162] The hydrogel material obtained in Example 17 was added with 1 mL of PBS to reach swelling equilibrium, and then transferred to a rotational rheometer. The shear rate sweep test proved that the hydrogel had shear thinning properties and good injectability.

[0163] Embodiment 35

[0164] The hydrogel material obtained in Example 26 was added with 1 mL of PBS to reach swelling equilibrium, and then transferred to a rotational rheometer. The shear rate sweep test proved that the hydrogel had shear thinning properties and good injectability.

[0165] Embodiment 36

[0166] The hydrogel material obtained in Example 29 was added with 1 mL of PBS to reach swelling equilibrium, and then transferred to a rotational rheometer. The shear rate sweep test proved that the hydrogel had shear thinning properties and good injectability.

[0167] Embodiment 37

[0168] After the solution 9 (200 μL) and solution 10 (20 μL) obtained in Example 14 were fully stirred and completely polymerized to form a hydrogel, 1 mL of PBS was added. When swelling equilibrium was reached, the solution was transferred to a UV cuvette, and its transmittance was characterized by characterizing its transmittance in the range of 400-800 nm.

[0169] See also Figure 7 , Figure 7 This is the UV-visible spectrum of the hydrogel prepared in Example 23 of the present invention. Figure 7 As shown in the figure, in most of the range of 400~800 nm, the transmittance of the hydrogel is above 90%, indicating that the hydrogel has good light transmittance. As a vitreous substitute, the hydrogel can ensure the normal transmission of light.

[0170] Embodiment 38

[0171] After the solution 11 (200 μL) and solution 12 (100 μL) obtained in Example 16 were fully stirred and completely polymerized to form a hydrogel, 1 mL of PBS was added. When swelling equilibrium was reached, the solution was transferred to a UV cuvette. The transmittance of the hydrogel in the range of 400-800 nm was above 90%. As a vitreous substitute, the hydrogel can ensure the normal transmission of light.

[0172] Embodiment 39

[0173] After the solution 13 (200 μL) and solution 14 (100 μL) obtained in Example 17 were fully stirred and completely polymerized to form a hydrogel, 1 mL of PBS was added. When swelling equilibrium was reached, the solution was transferred to a UV cuvette. The transmittance of the hydrogel in the range of 400-800 nm was above 90%. As a vitreous substitute, the hydrogel can ensure the normal transmission of light.

[0174] Embodiment 40

[0175] The solution 9 (200 μL) and solution 10 (20 μL) obtained in Example 14 were fully stirred to obtain a mixed solution which was transferred to a 2 mL centrifuge tube. After complete polymerization to form a hydrogel, the solution was freeze-dried and characterized by a scanning electron microscope.

[0176] See also Figure 8 , Figure 8This is a SEM scanning electron microscope image of the hydrogel prepared in Example 40 of the present invention; the results are as follows Figure 8 As shown, the hydrogel has a porous structure.

[0177] Embodiment 41

[0178] Solution 27 (200 μL) and solution 28 (40 μL) prepared in Example 28 were fully stirred, left to gel at room temperature, and freeze-dried before being characterized by scanning electron microscopy. The SEM characterization demonstrated that the hydrogel had a porous structure.

[0179] Embodiment 42

[0180] Solution 29 (200 μL) and solution 30 (200 μL) prepared in Example 29 were fully stirred, left to gel at room temperature, and freeze-dried before being characterized by scanning electron microscopy. The SEM characterization demonstrated that the hydrogel had a porous structure.

[0181] Embodiment 43

[0182] The hydrogels prepared by Example 12 and Example 14 were stabilized and placed in a 5 mL glass bottle, to which 1 mL of PBS buffer solution with a pH of 7.4 was added, and the mixture was cultured in a constant temperature incubator at 37 degrees Celsius. The PBS not absorbed by the gel was aspirated at regular intervals, and the gel was weighed. Subsequently, 1 mL of PBS was added again and the mixture was cultured in an incubator. This step was repeated until the mass of the hydrogel was reduced to about 0, and the swelling and degradation behavior of the hydrogel in PBS was characterized.

[0183] See also Fig. 9 , Fig. 9 The swelling and degradation of the hydrogels prepared in Examples 12 and 14 of the present invention are shown in FIG. Fig. 9 As shown, the hydrogel swells rapidly in PBS and remains stable for a long time without degradation, and can be used as a vitreous substitute to maintain long-term stability of intraocular pressure.

[0184] Embodiment 44

[0185] The hydrogels prepared by Example 18 and Example 20 were stabilized and placed in a 5 mL glass bottle, 1 mL of a PBS buffer solution with a pH of 7.4 was added thereto, and the solution was cultured in a constant temperature incubator at 37 degrees Celsius. The PBS not absorbed by the gel was aspirated at regular intervals, and the gel was weighed, and then 1 mL of PBS was added again and placed in an incubator for culture. This step was repeated until the mass of the hydrogel was reduced to about 0, and the swelling and degradation behavior of the hydrogel in PBS was characterized. The hydrogel swelled rapidly in PBS and remained stable for a long time without degradation, and could be used as a vitreous substitute to maintain long-term stability of intraocular pressure.

[0186] Embodiment 45

[0187] The hydrogel prepared by Example 22 and Example 24 was stabilized and placed in a 5 mL glass bottle, 1 mL of PBS buffer solution with a pH of 7.4 was added thereto, and the solution was cultured in a constant temperature incubator at 37 degrees Celsius. The PBS not absorbed by the gel was sucked out at regular intervals, and the gel was weighed, and then 1 mL of PBS was added again and placed in an incubator for culture. This step was repeated until the mass of the hydrogel was reduced to about 0, and the swelling and degradation behavior of the hydrogel in PBS was characterized. The hydrogel swelled rapidly in PBS and remained stable for a long time without degradation, and could be used as a vitreous substitute to maintain long-term stability of intraocular pressure.

[0188] Embodiment 46

[0189] Retinal pigment epithelial cells (RPE) were inoculated in a sterile 96-well plate (8000 cells / well, 200 μL DMEM / well), and then placed in a sterile incubator for culture. After 24 h, the old culture medium was discarded, and different concentrations of the extract of the hydrogel sample prepared in Example 12 were added to the wells (n=5). The extract was prepared by soaking 50 mg, 25 mg, 12.5 mg, 6.25 mg, 3.12 mg and 1.56 mg of the hydrogel prepared in Example 12 in 1 mL DMEM in a 5 mL glass bottle at 37 degrees Celsius for 24 h, then the liquid was aspirated and filtered to obtain the extract of the hydrogel sample prepared in Example 12 with different concentrations. The cell group cultured in DMEM was used as a control. After culturing for 24 h, the old culture medium was aspirated and 100 μL of 10% CCK-8 solution was added to each well. The cells were incubated in the incubator for 1 h, and then the absorbance of each sample well at 450 nm was detected using an enzyme-labeled instrument.

[0190] See also Fig.10 , Fig.10 The present invention provides an injectable hydrogel material for cytotoxicity to RPE cells. Fig.10 It can be seen that the experimental results show that the degradation products of the hydrogel have no cytotoxicity to normal retinal pigment epithelial cells, proving that the hydrogel can be used in eye surgery as a vitreous substitute.

[0191] Embodiment 47

[0192] Retinal pigment epithelial cells (RPE) were inoculated in a sterile 96-well plate (8000 cells / well, 200 μL DMEM / well), and then placed in a sterile incubator for culture. After 24 h, the old culture medium was discarded, and different concentrations of the extract of the hydrogel sample prepared in Example 28 were added to the wells (n=5). The method for preparing the extract is as follows: 50 mg, 25 mg, 12.5 mg, 6.25 mg, 3.12 mg and 1.56 mg of the hydrogel prepared in Example 28 were soaked in 1 mL DMEM in a 5 mL glass bottle at 37 degrees Celsius for 24 h, and then the liquid was aspirated and filtered to obtain the extract of the hydrogel sample prepared in Example 28 with different concentrations. The cell group cultured in DMEM was used as a control. After 24 hours of culture, the old culture medium was aspirated and 100 μL of 10% CCK-8 solution was added to each well. The cells were incubated in the incubator for 1 hour, and then the absorbance of each sample well at 450 nm was detected by a microplate reader. The results showed that the degradation products of the hydrogel had no cytotoxicity to normal retinal pigment epithelial cells, proving that the hydrogel can be used as a vitreous substitute in ocular surgery.

[0193] Embodiment 48

[0194] Retinal pigment epithelial cells (RPE) were inoculated in a sterile 96-well plate (8000 cells / well, 200 μL DMEM / well), and then placed in a sterile incubator for culture. After 24 h, the old culture medium was discarded, and different concentrations of the extract of the hydrogel sample prepared in Example 29 were added to the wells (n=5). The extract was prepared by soaking 50 mg, 25 mg, 12.5 mg, 6.25 mg, 3.12 mg and 1.56 mg of the hydrogel prepared in Example 29 in 1 mL DMEM in a 5 mL glass bottle at 37 degrees Celsius for 24 h, then the liquid was aspirated and filtered to obtain the extract of the hydrogel sample prepared in Example 29 with different concentrations. The cell group cultured in DMEM was used as a control. After 24 hours of culture, the old culture medium was aspirated and 100 μL of 10% CCK-8 solution was added to each well. The cells were incubated in the incubator for 1 hour, and then the absorbance of each sample well at 450 nm was detected by a microplate reader. The results showed that the degradation products of the hydrogel had no cytotoxicity to normal retinal pigment epithelial cells, proving that the hydrogel can be used as a vitreous substitute in ocular surgery.

[0195] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An injectable hydrogel material, characterized in that: The injectable hydrogel material is formed by a polymer; the polymer includes a cyanoalkyl hydrazide functionalized polymer and a polymer containing an aldehyde functional group; the cyanoalkyl hydrazide functionalized polymer includes a cyanoalkyl hydrazide functionalized polysaccharide polymer and / or a cyanoalkyl hydrazide functionalized multi-arm polyethylene glycol; The polymer containing aldehyde functional groups includes aldehyde functionalized polysaccharide and / or aldehyde functionalized multi-arm polyethylene glycol; The mass ratio of the cyanoalkyl hydrazide functionalized polymer to the polymer containing aldehyde functional groups is 1:(0.1-10); The injectable hydrogel material acts as a vitreous substitute.

2. The injectable hydrogel material according to claim 1, characterized in that: The cyanoalkyl hydrazide functionalized polymer includes one or more of cyanoalkyl hydrazide functionalized hyaluronic acid, cyanoalkyl hydrazide functionalized sodium hyaluronate, cyanoalkyl hydrazide functionalized alginate, cyanoalkyl hydrazide functionalized sodium alginate, cyanoalkyl hydrazide functionalized four-arm polyethylene glycol, cyanoalkyl hydrazide functionalized six-arm polyethylene glycol and cyanoalkyl hydrazide functionalized eight-arm polyethylene glycol; The polymer containing aldehyde functional groups includes one or more of aldehyde functionalized dextran, aldehyde functionalized hyaluronic acid, aldehyde functionalized sodium hyaluronate, aldehyde functionalized four-arm polyethylene glycol, aldehyde functionalized six-arm polyethylene glycol and aldehyde functionalized eight-arm polyethylene glycol; The cyanoalkyl hydrazide functionalized polymer is a cyanoacetohydrazide functionalized polymer.

3. The injectable hydrogel material according to claim 1, characterized in that: The cyanoalkyl hydrazide functionalized polymer is selected from one or more structures represented by formula (I-1) to formula (I-3): m, n, p and q are degrees of polymerization, and m, n, p and q are each independently an integer of 20 to 300; e in formula (I-3) is a repeating unit, and e is an integer of 10 to 100.

4. The injectable hydrogel material according to claim 1, characterized in that: The polymer containing aldehyde functional groups is selected from one or more structures represented by formula (II-1) to formula (II-3): a, b, c and d are degrees of polymerization, and a, b, c and d are each independently an integer of 20 to 300; in formula (II-3), f is a repeating unit, and f is an integer of 10 to 100.

5. A method for preparing the injectable hydrogel material according to claim 1, characterized in that: The following steps are involved: S1) providing a cyanoalkyl hydrazide functionalized polymer solution and a polymer solution containing an aldehyde functional group; S2) The polymer solution functionalized with cyanoalkyl hydrazide is mixed with the polymer solution containing aldehyde functional groups to undergo a cross-linking reaction to obtain an injectable hydrogel material.

6. The preparation method according to claim 5, characterized in that: The concentration of the cyanoalkyl hydrazide functionalized polymer in the cyanoalkyl hydrazide functionalized polymer solution is 5 to 100 mg / mL; The concentration of the polymer containing aldehyde functional groups in the polymer solution containing aldehyde functional groups is 50-150 mg / mL; The solvents in the cyanoalkyl hydrazide functionalized polymer solution and the polymer solution containing aldehyde functional groups are independently selected from one or more of water, physiological saline and buffer solution.

7. The preparation method according to claim 5, characterized in that: The mixing temperature is 4°C to 37°C; the cross-linking reaction temperature is 4°C to 37°C; and the cross-linking reaction time is 5 to 20 min.

8. Use of the injectable hydrogel according to any one of claims 1 to 4 or the injectable hydrogel prepared by the preparation method according to any one of claims 5 to 7 as a vitreous substitute.

Citation Information

Patent Citations

  • Preparation method of injectable hydrogel precursor solution, injectable hydrogel and application of injectable hydrogel

    CN111171339A